Relationship Between Organizational Injustice and Work Interference with Family: The Role of Social Support. (December 2019) - Kumar, Aneel; Ali Arain, Ghulam; Ahmed Channa, Khalil
Abstract: This study investigates the moderating role of social support (i.e., supervisor, co-workers and the family) in the relationship between organizational injustice (i.e., distributive and procedural) and work interference with family (WIF; i.e., strain and behaviour based). Quantitative data were collected from employees working in public sector health-care organizations of Pakistan through survey questionnaires ( N = 255). This study finds significant effects of distributive and procedural injustice in engendering the negative experiences of strain- and behaviour-based WIF, in the employees of health-care organizations. The moderating effect of co-worker and family support provided mixed results. The supervisory social support was not found as a moderator. Findings of this study suggest that health-care organizations should pay serious attention to the ineffective work family policies and procedure to develop a family-friendly work environment. The supervisors should be given a role in work family policies and procedure development. The mitigating effect of co-workers' support showed that the employees should be provided with proper knowledge on the policies and procedures of their organizations. The support of family members can also be either benign or harmful.